Automatic Constant Volume Algorithm of Volumetric Flask Based on SAM 2 - Xu, Lujian; Li, Meng; Yu, Hongliang (Chinese Control and Decision Conference, 2025)
In the chemical analysis process, constant volume is a critical step. However, manual methods of identifying liquid levels and scale lines through visual recognition have the following problems: cumbersome processes, low accuracy in volume determination, and low efficiency. An automatic constant volume algorithm is proposed in this paper. First of all, using the mesh point segmentation of Segment Anything Model 2 (SAM2) and Line Segment Detector (LSD), the scale line recognition algorithm is designed. Secondly, combined with the box segmentation of SAM2 and connected component analysis, the liquid level recognition algorithm is designed. Complete automatic constant volume by identifying whether the liquid level reaches the position of the scale line. The experimental results show that the precision of the scale line recognition algorithm based on SAM2 is 98.6%, and the precision of liquid level recognition algorithm is 97.3%. Compared with the traditional visual algorithm, it has higher precision, and has great application value.